Quality of Evidence Supporting the Role of Supplement Curcumin for the Treatment of Ulcerative Colitis: An Overview of Systematic Reviews - Hongshuo Shi; Dan Wang; Wenqiang Chen; Yinghao Li; Guomin Si; Tiantian Yang (Gastroenterology Research and Practice)
Objectives. Curcumin is a potential complementary treatment for ulcerative colitis (UC). This overview systematically summarizes and evaluates the existing evidence of curcumin in the treatment of UC. Methods. Two researchers searched seven databases for systematic reviews (SRs)/meta-analyses (MAs) which are about randomized controlled trials (RCTs) on curcumin for UC. Two researchers use the Assessment of Multiple Systematic Reviews 2 (AMSTAR-2), the Risk of Bias in Systematic Reviews (ROBIS) scale, the list of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), and the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system to assess the included SRs/MAs. Results. Seven published SRs/MAs were included in our study. According to the results of the AMSTAR-2 assessment, all SRs/MAs are considered to be of very low quality. According to the ROBIS evaluation results, no SR/MA has been assessed as a low risk of bias. According to the results of the PRISMA checklist assessment, no SR/MA has been fully reported on the PRISMA checklist. According to GRADE, a total of 19 outcome indicators extracted from the included SRs/MAs were evaluated. The quality of evidence was 10 moderate, 6 low, and 3 very low. Conclusions. Curcumin may be an effective and safe complementary treatment for UC. However, further standard and comprehensive SRs/MAs and RCTs are needed to provide an evidence-based medical rationale for this.